Anti-CD44 mAb for the treatment of B-cell chronic lymphocytic leukemia and other hematological malignancies: evaluation of WO2013063498. (July 2014) - D'Arena, Giovanni; Calapai, Gioacchino; Deaglio, Silvia
<x xml:space="preserve">Abstract</x> Introduction: The CD44 transmembrane glycoprotein family mediates cellular responses to the microenvironment through binding of hyaluronic acid (HA) and other proteins of the extracellular matrix. These interactions start intracellular signaling cascades that foster tumor growth, survival and spread. Areas covered: The patent concerns the use of a humanized anti-CD44 mAb (RG7356) to treat patients with aggressive forms of chronic lymphocytic leukemia (CLL). The RG7356 humanized antibody was designed to bind the constant region of CD44, preventing binding with HA. The interruption of this circuit in vitro is followed by the induction of caspase-dependent apoptosis in leukemic cells. In agreement with a functional association between CD44 and zeta-associated protein of 70 kDa (ZAP-70) in activating intracellular signaling, the strongest effects were observed in ZAP-70+ CLL cells, generally associated to a poor prognosis. Furthermore, these effects were confirmed using in vivo models, where CLL cells were xenografted in immunocompromised mice. Expert opinion: In summary, these studies suggest that this new humanized mAb may provide additional clinical benefit to CLL patients receiving current standard treatments, specifically to those with a more aggressive disease.